Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1093/oxfordjournals.jbchem.a123929
|View full text |Cite
|
Sign up to set email alerts
|

Human T Cell L-Plastin Bundles Actin Filaments in a Calcium Dependent Manner1

Abstract: The amino acid sequences deduced from cDNA analyses revealed that human leucocyte L-plastin phosphorylated in response to interleukin 1, 2 closely resembles a chicken intestinal microvilli protein, fimbrin, that bundles actin filaments [de Arruda et al. (1990) J. Cell Biol. 111, 1069-1079]. In the present work, it was observed that unphosphorylated L-plastin isolated from human T cells bundled F-actin just as fimbrin does. L-Plastin acted on T cell beta-actin, but hardly acted on muscle alpha-actin or chicken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
1
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(148 citation statements)
references
References 0 publications
7
138
1
1
Order By: Relevance
“…Calcium insensitivity was also reported for chicken fimbrin (Bretscher, 1981) and S. pombe Fim1p (Nakano et al, 2001). By contrast, plastins from mammalian cells (Namba et al, 1992;Lin et al, 1994) and Dictyostelium (Prassler et al, 1997) have been shown to be calcium sensitive. Another study reported that a fimbrin-like protein from T. pyriformis lacks EF-hand domains (Watanabe et al, 2000).…”
Section: Fim5 Is a Bona Fide Actin Bundling Factormentioning
confidence: 78%
“…Calcium insensitivity was also reported for chicken fimbrin (Bretscher, 1981) and S. pombe Fim1p (Nakano et al, 2001). By contrast, plastins from mammalian cells (Namba et al, 1992;Lin et al, 1994) and Dictyostelium (Prassler et al, 1997) have been shown to be calcium sensitive. Another study reported that a fimbrin-like protein from T. pyriformis lacks EF-hand domains (Watanabe et al, 2000).…”
Section: Fim5 Is a Bona Fide Actin Bundling Factormentioning
confidence: 78%
“…It is known that increased calcium concentrations negatively regulate the actin-bundling activity of LCP1 (46). It has been recently shown that LCP1 contains a switch helix structure that, in the presence of calcium, tightly binds to EF-hand motifs (47).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it seems to interact more tightly with certain actin binding proteins that may function at the leading edge of crawling cells. Ezrin (19), profilin (20), thymosin ␤ 4 (21), and L-plastin (22) bind more strongly to ␤-actin than ␣-actin. A capping protein, ␤-cap 73, may cap the barbed end in an isoform-specific manner (23).…”
Section: Discussionmentioning
confidence: 99%